2019
DOI: 10.12809/hkmj187745
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning by toxic plants in Hong Kong: a 15-year review

Abstract: has a great diversity of plants, many of which are toxic to humans. The aim of this study was to identify the plant species most commonly involved in cases of plant poisoning in Hong Kong and to provide clinicians with a reference tool for the diagnosis and management of plant poisoning. Methods: We retrospectively reviewed all plant poisoning cases referred to the Hospital Authority Toxicology Reference Laboratory from 1 January 2003 to 31 December 2017. Demographics, clinical presentation, laboratory finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Overall, in line with other reports on G. elegans, gelsenicine in this study triggered respiration failure 10 without gastrointestinal toxicity, hepatotoxicity, nephrotoxicity, and cardiotoxicity. 7 Therefore, these data suggested that gelsenicine is an acute neurotoxin that can lead to death; but it did not produce marked cumulative toxic effects and substantial organ damage in subacute toxicity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, in line with other reports on G. elegans, gelsenicine in this study triggered respiration failure 10 without gastrointestinal toxicity, hepatotoxicity, nephrotoxicity, and cardiotoxicity. 7 Therefore, these data suggested that gelsenicine is an acute neurotoxin that can lead to death; but it did not produce marked cumulative toxic effects and substantial organ damage in subacute toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…6 However, G. elegans is highly toxic with a narrow therapeutic window, and clinical studies related to it are greatly limited. 7,8 Cases of unintentional poisoning, food contamination, and suicides related to G. elegans are still being reported. [9][10][11] Gelsenicine is a gelsedine-type indole alkaloid of G. elegans.…”
Section: Introductionmentioning
confidence: 99%
“…The MFDS has designated 21 poisonous herbs, which are off-limits for purchase for non-licensed persons and are supplied only to TKM clinics [ 34 ]. Poisonous herbs may cause severe side effects or even death if taken above a certain level [ 35 ]. Thus, they need to be managed separated from normal herbal materials by licensed TKM pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Even though, like most plant organs, they contain Vit C, their potential toxicity makes their consumption on a constant basis unfeasible, although these could have been drunk occasionally as a therapeutic remedy [66]. However, most of these vegetable organs contain turpentine and other toxic compounds that can cause various health problems, including hepatotoxicity [133]. Moreover, in pregnant women, both juniper and pine needles can pose risks to the developing fetus as the toxic substances present in needles can cross the placenta and potentially cause harm, while laboratory and animal studies have suggested that Juniperus and Pinus species share similar chemistries and have antifertility effects in both males and females [134].…”
Section: Sources Of Vitamin C For M3hmentioning
confidence: 99%